DERIVATIONAL AND INFLECTIONAL MORPHEME IN ENGLISH LANGUAGE - Rizky Aziz, M.; Libra, Intan; Putri, Devita; Purwanto, Tri; Chusna, Nisaul (JOSAR (Journal of Students Academic Research), 2019)
This paper talks about the morphology which study or words how they are formed and their relationship to other words in the same language. However, we focus on the derivational and inflectional morpheme, which has some aspects (suffixes and prefixes) and how they are categorized. In the context of Natural Language Processing, the question of how the boundaries of merging, derivation, and inflection with each other and with areas outside morphology can be determined and gained new relevance. This work develops a framework that can provide background for answers at the same time and is interesting, both theoretically and practically. On the basis of a thorough discussion of the literature, language-independent definitions are given for compounding, derivation, and inflection. We are as the writers, we look for the references using the internet.research method The descriptive method is one of the methods we made to collect data, because our research formed a theoretical explanation different reference sources. Some of the data that we have obtained is the result of many references on the internet that we have filtered and selected according to the chapters or material we have examined and to using the descriptive method the researcher also uses the content analysis method, the discussion of a study using this method, is in-depth which will study a theory that has existed in the past and present by comparing which is more relevant to be used for the general public. There are some differences between inflectional and derivational morphemes. First, inflectional morphemes never change the grammatical category (part of speech) of a word. derivational morphemes often change the part of speech of a word. Thus, the verb read becomes the noun reader when we add the derivational morpheme -er. It is simply that read is a verb, but reader is a noun. However, some derivational morphemes do not change the grammatical category of a word.